A Rare Manifestation of Asymptomatic Ebstein’s Anomaly with Tricuspid Valve Endocarditis - Carmel Moazez; Vicken Zeitjian; Christian Breburda; Ranjini Roy (Case Reports in Cardiology)
Ebstein’s anomaly is a rare congenital heart disease that presents with apical displacement of the septal and posterior leaflets of the tricuspid valve. It has a wide spectrum of clinical presentations and has been shown to manifest itself any time from birth to adulthood. Our patient is a 43-year-old male with a history of intravenous heroin abuse who presented to the emergency department with worsening shortness of breath and lower extremity edema. He denied any prior cardiac history. A transthoracic echo showed normal left ventricular function, but a large 2.2 × 2.1 cm echodensity on the septal leaflet of the tricuspid valve consistent with vegetation with severe tricuspid regurgitation and probable leaflet perforation. It also demonstrated severe right heart enlargement with atrialization of the right ventricle and apical displacement of the tricuspid valve consistent with Ebstein’s anomaly. This is a rare case of an adult who presented with asymptomatic Ebstein’s anomaly. There have been few reports of tricuspid valve endocarditis with Ebstein’s anomaly in the literature. To our knowledge, this represents the fifth reported case of a new diagnosis of Ebstein’s anomaly in the setting of endocarditis and the second case of Ebstein’s anomaly and endocarditis in an intravenous drug abuser.